A survey of exercise advice and recommendations in United Kingdom paediatric cardiac clinics. (16th January 2017) - Williams, Craig A.; Gowing, Lucy; Horn, Richard; Stuart, Alan Graham
Abstract: Background: Physical activity and exercise have important health benefits for children and adolescents with CHD. The objective of this study was to survey the provision of advice and recommendations in United Kingdom paediatric CHD clinics. Methods: A three-page questionnaire was sent out to paediatric cardiac consultants in the United Kingdom, paediatric consultants with expertise in cardiology, and nursing staff (Paediatricians with Expertise in Cardiology Special Interest Group), as well as all members of the British Congenital Cardiovascular Association. The aim of this questionnaire was to determine the extent and scope of current information provision and to assess the importance that clinicians place on this advice. Results: There were 68 responses in total, and the data showed that, of these, 24 (36%) clinicians had never provided paediatric CHD patients with written advice about exercise. Only 27 (39%) clinicians provided physical activity advice at every appointment. Lack of time during consultation (n=39, 56.9%), lack of training (n=38, 55.2%), and uncertainty about appropriate recommendations (n=38, 55.2%) were identified as the main factors preventing clinicians from providing patients with advice about physical activity. Conclusion: Although healthcare providers consider physical activity to be very important, the provision of clear, specific advice and recommendations is underutilised; therefore, more education and provision of resources to support the promotion of exercise need to be provided to clinicians and their support teams.